دور التحول الرقمي في تحسين استراتيجيات المصارف التجارية في جذب الودائع - القدارأ.وائل صبري (Aljameai)
المستخلص: هدفت هذه الدراسة إلى بيان أهمية دور التحول الرقمي في تحسين استراتيجيات المصارف التجارية في جذب الودائع من خلال التعرف على أهم الخدمات الالكترونية الحديثة التي يمكن استخدامها في المجال المصرفي، ومدى إمكانية استغلال التكنولوجيا الرقمية في خلق فرص لتقديم خدمات مبتكرة وإبداعية بعيدة عن الطرق التقليدية في تقديم الخدمات المصرفية، والتي ستساهم بدورها في خلق حالة من الرضى والقبول لدى جمهور المودعين اتجاه خدمات المصرف. ومن أجل تحقيق هذا الهدف فقد اعتمدت الدراسة في جمع البيانات الأولية عن طريق الاستبانة، والذي من خلاله سيقوم الباحث بجمع إجابات المستهدفين؛ بهدف استخلاص النتائج. وفي سبيل اختبار الفرضيات سيتم استخدام برنامج ( (SPSS للتحليل الإحصائي . وقد توصلت الدراسة إلى نتائج عدة، من أهمها عمل المصرف على إرساء مناخ رقمي يركز على تغير سلوكيات الأفراد وإضافة قيم جديدة، ويمثل التحول الرقمي للمصرف أحد المرتكزات الأساسية لتوفير الوقت والجهد في التفاعل مع عملائه. Abstract: The study aims to demonstrate the importance of the role of digital transformation in improving commercial banks’ strategies in attracting deposits by identifying the most important modern electronic services that can be used in the banking sector and the extent to which digital technology can be exploited to create opportunities to provide innovative and creative services away from traditional methods of providing banking services, which will in turn contribute to creating a state of satisfaction and acceptance among depositors towards the bank’s services. In order to achieve this goal, the study relied on collecting primary data for this study through a questionnaire, through which the researcher will collect the answers of the target groups, with the aim of extracting the results. In order to test the hypotheses, the SPSS program will be used for statistical analysis. The study reached several results, the most important of which is that the bank is working to establish a digital climate that focuses on changing the behavior of individuals and adding new values. The digital transformation of the bank represents one of the basic pillars for saving time and effort in interacting with its customers.